The Effects Of Acaricide Dipping Methods On Bulb Mite [Rhizoglyphus Echinopus (Fumouze & Robin) (Acari: Astigmata)] That Harmfull On Garlic - Cilbircioglu, Cihan; Cobanoglu, Sultan (Aperta, 2018)
Rhizoglyphus echinopus (Fumouze & Robin) (Acari: Astigmata) is the most important harmful mite species in garlic (Alliaceae: Allium sativum L.) areas in Kastamonu. This mite causes darkening and decaying especially in the underground part of the garlic, causing significant damage. In this study, the effects of acaricide Azadirachtin indica, Abamectin and Hexythiazox were investigated. on the R. echinopus damage of garlic heads during the garlic cultivation period. For this purpose, garlic seeds were dipped in acaricide solutions and later planted. Whether or not the effects of the acaricides on the harmful mite concentration in the soil were tried to be revealed by the exit rates of the plants. Trials were carried out in two different locations from garlic farming areas in Kastamonu province during the 2015-2016 vegetation period. Each extract was tested in 16 plots by four repetitive and four parcels were identified as controls and no application was made to these parcels. As a result were identified that Azadirachtin indica, Abamectin and Hexythiazox were not significantly different from control, no effect on R. echinopus in the head of the garlic and has been determined that natural equilibrium has been established in the control plots.
Keywords: 2. Zero hunger